TERJEMAH DWIBAHASA PENGANTAR KE ARAH PENDEKATAN LINGUISTIK - NURLAILA NURLAILA (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2010)
Translation is a process of translating messages from the source language to the target one by preserving the intended meaning of the original sources. This can be achieved by following three main stages: analyzing the message of the source language, translating and reconstructing message by re-expressing in target language so that the translated version is acceptable and readable in terms of form and style of the target language. Since source and target languages have their own type and grammatical rules, a good translations, therefore, should use natural forms of target language and communicate as much as possible the meaning intended by the source language into target language while preserving the ‘dynamics’ source language texts.Kata kunci: terjemah, linguistik, bahasa sumber, bahasa sasaran